Diagnostic utility of lung ultrasound in preterm neonates with respiratory distress at a tertiary neonatal intensive care unit in the Western Cape - Mpisane-Jama, Fefekazi (Department of Paediatrics and Child Health, 2025)
Background: Accumulating data suggest the potential for lung ultrasound (LUS) to diagnose lung pathology and predict the need for surfactant administration in preterm babies, but there are no published data from South Africa. Objectives: The objectives were to describe LUS diagnoses and outcomes in preterm babies receiving non-invasive respiratory support in a South African neonatal unit, and to compare LUS with clinical diagnoses and surfactant administration. Methods: We conducted a prospective, observational study of babies 27–34 weeks' gestation, birth weight ≥ 800 grams, receiving non-invasive respiratory support who had LUS at age ≤ 3 hours. Surfactant was administered at fraction of inspired oxygen (FiO2) 0.35–0.45 and was not influenced by LUS findings. Results: Over a 4-month period, 51 babies were included – eight (16%) received surfactant, all of whom had respiratory distress syndrome (RDS) as their only clinical diagnosis, compared to overlapping diagnoses in the non-surfactant group; RDS (93%), TTN (16%) and pneumonia (14%). Lung ultrasound suggested less RDS in the non-surfactant group (42% vs. 88%; p=0.002), and more TTN (79% vs. 38%; p=0.002) and TTN plus pneumonia (65% vs. 25%; p=0.03). The LUS score (LUSS) predicted surfactant administration (Area under the curve 0.8 [95% confidence interval 67-94%]). A LUSS of 7 had the best combined sensitivity (75%) and specificity (72%) but low positive predictive value (33%). A LUSS of 8 identified 8/43 (19%) additional babies for surfactant who did not need treatment. Conclusion: Lung ultrasound suggested a higher frequency of alternative and additional diagnoses than clinical assessment but was not an adequate single indicator of surfactant requirement, compared to FiO2 threshold. The high frequency of LUS features of TTN in the non-surfactant group, highlights the need to consider TTN as an alternative diagnosis in similar preterm neonates.